(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
DOAS is a philosophy to pick section for particular thin band ingestion structures in the UV and recognizable phantom locale. Measurement is based on absorption spectroscopy in the UV and visible wavelength range.